Bussiness Model Canvas: Glow In The Dark Marker Pen (GoGlow) / Wan Mohd Zawir Wan Mokhtar - Wan Mokhtar, Wan Mohd Zawir (2020)
The company target the users from students, office workers and teaching staff such as lecturers and teachers. Lecturers and office worker usually uses marker pen when teaching and presenting in the class and office respectively. The glow in the dark marker pen will help this users to write in the dark when the light is turn off. In addition, the users will get more benefit with this product where the others people can see the writing since the ink can be seen clearly in the dark